Regenerative SiC frequency converter with compact Z-source DC-link and sinusoidal output voltage - Lechler, Martin; Piepenbreier, Bernhard (SPEEDAM, 2012)
In this paper a new Z-source frequency converter with silicon carbide (SiC) components is presented. Both, the motor side and the line side converter, contain SiC-VJFETs using the reverse-conducting capability for freewheeling. The application of SiC transistors with their low switching losses, allows high switching frequencies (up to 125 kHz), so the volume of the DC-link and filter components is reduced. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.regene
Keywords: AC/AC converter; Gate Drive Unit; Silicon Carbide (SiC) VJFET; Z-Source topology

Z-Source Drive Inverter using modified SVPWM for low Output Voltage and regenerating Operation - Lechler, Martin; von Zimmermann, Moritz; Piepenbreier, Bernhard (EPE 2009 Barcelona, 2009)
Z-source inverters, consisting of both inductors and capacitors as DC-link components, provide unique boost capability with simple structure needing no additional switching elements. Due to complex operation modes of the Z-source inverter compared to a conventional inverter, boost operation, light load and regenerating operation cannot be achieved using common space-vector pulse width modulation. This paper proposes a modified SVPWM, derived from the known equations, to overcome this limitation. Besides, equations to control the output behaviour for all operating modes, such as buck, boost and regenerating operation, are given in detail. Finally, experimental results are presented.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEEAS.zsourc
Keywords: AC/AC converter; Adjustable speed drive; Drive; Emerging topology